Overview of analytical hierarchy process decision making method for construction risk management - Putri Zulaiha, Razi; Mohamad Idris, Ali; Noram Irwan, Ramli (IOP Publishing, 2019)
The construction industry is one of the industries that currently gave an overwhelming effect to the booster of the developing country. Construction field is one of the areas that need immediate decision during the planning, design or construction stage. A construction project in a broader context is the involvement of multiple construction practitioners with an aim to ensure that the project complete within the time frame and budget with assured quality. In ensuring smoothness of the construction project, a multi-criteria decision making (MCDM) technique as a systematic tool has been used widely, namely Analytical Hierarchy Process (AHP). Based on the 40 journal articles, questions of which civil engineering field does AHP mostly employed as decision making tools in any of risk occurrence may be answered. Results revealed that thirteen (13) various civil engineering field was discovered adopting AHP as decision making assessment method and company and managerial, road highway project and building construction remarked the core field attracted much interest.